2014
DOI: 10.1111/pme.12499
|View full text |Cite
|
Sign up to set email alerts
|

Patient Recall of Health Care Provider Counseling for Opioid-Acetaminophen Prescriptions

Abstract: Patients infrequently recall counseling from providers on topics that are important to prevent harm from opioid-acetaminophen prescriptions. Future patient-centered clinical research should target identifying optimal strategies to convey these critical messages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Non-pharmacologic pain management approaches are frequently not covered by health insurance, leaving disadvantaged cLBP patients without access to some of the most widely recommended treatment options [51]. Additionally, patients may not be appropriately informed about low efficacy and high risk of side effects with opioid use [44, 29]. Low levels of education have also been linked to increased drug poisoning and opioid-related mortality [25, 38].…”
Section: Discussionmentioning
confidence: 99%
“…Non-pharmacologic pain management approaches are frequently not covered by health insurance, leaving disadvantaged cLBP patients without access to some of the most widely recommended treatment options [51]. Additionally, patients may not be appropriately informed about low efficacy and high risk of side effects with opioid use [44, 29]. Low levels of education have also been linked to increased drug poisoning and opioid-related mortality [25, 38].…”
Section: Discussionmentioning
confidence: 99%
“…A need to observe social distance amid the COVID-19 pandemic may hinder effective communication of information related to patient's treatment or medication. Even before the COVID-19 pandemic, patients often misunderstand the content of pharmacists' recommendations during counselling or they tend to forget the given information (McCarthy et al, 2014). Therefore, the provision of reading materials may complement pharmacists' counselling.…”
Section: Provision Of Reading Materialsmentioning
confidence: 99%
“…Discussion of drug name, purpose, and side effects are often considered minimum expectations for counseling by HCP, especially pharmacists. 36 While some studies found that side effects were commonly discussed with patients, 8 , 13 , 15 , 22 , 37 some HCP do not consistently discuss them with patients. 38 , 39 Additionally, several patients often did not receive information regarding mitigation strategies or further options for managing bothersome side effects.…”
Section: Discussionmentioning
confidence: 99%